The risk of venous thromboembolism in patients with hepatitis C - Ambrosino, Pasquale; Tarantino, Luciano; Criscuolo, Livio; Nasto, Aurelio; Celentano, Aldo; Di Minno, Matteo Nicola Dario (Thrombosis and Haemostasis, 2016)
Some studies suggest that patients with hepatitis C virus (HCV) infection have an increased risk of deep venous thrombosis (DVT) and pulmonary embolism (PE). Unfortunately, available data on this association are contrasting. A systematic review and meta-analysis of literature studies was performed to evaluate the risk of venous thromboembolism (VTE) associated with HCV. Studies reporting on VTE risk associated with HCV were systematically searched in the PubMed, Web of Science, Scopus and EMBASE databases. Six studies (10 data-sets) showed a significantly increased VTE risk in 100,364 HCV patients as compared with 8,471,176 uninfected controls (odds ratio [OR]: 1.900; 95 % confidence interval [CI]: 1.406, 2.570; p<0.0001). These results were confirmed when specifically considering the risk of DVT (6 studies, OR: 1.918; 95 %CI: 1.351, 2.723; p<0.0001), whereas a trend towards an increased risk of PE was documented in HCV patients (4 studies, OR: 1.811; 95 %CI: 0.895, 3.663; p=0.099). The increased VTE risk associated with HCV infection was consistently confirmed when analysing four studies reporting adjusted risk estimates (OR: 1.876; 95 %CI: 1.326, 2.654; P<0.0001), and after excluding studies specifically enrolling populations exposed to transient risk factors for VTE (4 studies, OR: 1.493; 95 %CI: 1.167, 1.910; p=0.001). Meta-regression models suggested that age and male gender may significantly impact on the risk of VTE associated with HCV-positivity. Results of our metaanalysis suggest that HCV-infected subjects may exhibit an increased risk of VTE. However, further high quality studies are needed to extend and confirm our findings.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Hepatitis C; viral hepatitis; deep venous thrombosis; pulmonary embolism; venous thromboembolism